InCIEC 2013 2014
DOI: 10.1007/978-981-4585-02-6_77
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanoparticle-Based XLPE/SiO2/TiO2 and XLPE/SiO2 Nanocomposites: Nanoscale Hybrid Assembling, Mechanics and Thermal properties

Abstract: This report demonstrates the successful use of hybrid nanoparticles of SiO 2 and TiO 2 in cross-linked polyethylene (XLPE) and reports the comparison of mechanical properties and thermal stability of XLPE/SiO 2 /TiO 2 nanocomposites compared to XLPE/SiO 2 , at different filler concentrations and with neat XLPE. In the present system of XLPE/SiO 2 nanocomposites, tensile strength and thermal stability show an increasing trend with nanoparticles, followed by a decaying trend at higher filler loading, whereas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Nanofillers such as SiO 2 , TiO 2 , Al 2 O 3 , CaCO 3 , MgO, ZnO, and carbon black are commonly used to enhance the electrical properties (space charge accumulation, breakdown strength, dielectric loss, PD, etc.) of XLPE. The geometric shape, dispersion state, particle size, and surface quality of the filler affect the entire property of the nanocomposites. , XLPE nanocomposites can be fabricated from different ways such as in situ polymerization, sol–gel processing, solution casting, and melt mixing. , The reason behind the changes in electrical properties of XLPE nanocomposites are shown Table S4 in the Supporting Information. Depending on the geometry or dimensions of the particles, four main types of fillers are distinguished.…”
Section: Xlpe Nanocompositesmentioning
confidence: 99%
“…Nanofillers such as SiO 2 , TiO 2 , Al 2 O 3 , CaCO 3 , MgO, ZnO, and carbon black are commonly used to enhance the electrical properties (space charge accumulation, breakdown strength, dielectric loss, PD, etc.) of XLPE. The geometric shape, dispersion state, particle size, and surface quality of the filler affect the entire property of the nanocomposites. , XLPE nanocomposites can be fabricated from different ways such as in situ polymerization, sol–gel processing, solution casting, and melt mixing. , The reason behind the changes in electrical properties of XLPE nanocomposites are shown Table S4 in the Supporting Information. Depending on the geometry or dimensions of the particles, four main types of fillers are distinguished.…”
Section: Xlpe Nanocompositesmentioning
confidence: 99%
“…Engagement of nanofillers with XLPE has further exposed the enhancement of the properties of the mixture and reduced the incompatibility issue between matrix and inorganic fillers [1], [2]. Studies have shown that the incorporation of nanofillers, such as silica (SiO 2 ), zinc oxide (ZnO), calcium carbonate (CaCO 3 ), silicon carbide (SiC), boron (BN), titanium oxide (TiO 2 ), and aluminium oxide (Al 2 O 3 ) has the ability to modify the dielectric properties of polyethylene [1], [3]- [6] and improve the mechanical and thermal properties of the nanocomposites [2], [7], [8]. Study on the adoption of modified nanoparticles in nanocomposites blend was found to be able to assist in providing higher compatibility between polymer and nanofiller [9].…”
Section: Introductionmentioning
confidence: 99%